Acute Oral Toxicity and Histophatological Study of Ethanol Extract and Fractions of Etlingera elatior Flowers in Mice - Inayatush Sholihah; Nestri Handayani; Novita Dhewi Ikakusumawati; Safna Bina Nusriya (JURNAL FARMASI DAN ILMU KEFARMASIAN INDONESIA, 2025)
Background: Etlingera elatior (Jack) R.M. Sm or Kecombrang Flower had been used traditionally to enhance the taste of food. Some studies reported its pharmacological activities such as antioxidant, anti-inflammatory, antimicrobial, and anticancer. However, its safety has not yet been reported explicitly. Objective: To investigate the acute oral toxicity, macropathological and histopathological changes of 96% ethanol extract, n-hexane, ethyl acetate and methanol-water fractions of Etlingera elatior flowers in Balb/C mice. Methods: The 96% ethanol extract, n-hexane, ethyl acetate and methanol-water (3:7) fractions were given to mice with 4 dose levels (75, 150, 300, and 600 mg/Kg body weight). Single oral administration of them was done on the first day of the test and the mice were then observed in 14 consecutive days. The control group received Na-CMC 0,3%. Changes in behavior, mortality rate, body weight, macropathology and histopathology of kidneys and liver were assessed. Results: No signs of toxicity or mortality were observed when mice were exposed to the 96% ethanol extract, n-hexane, ethyl acetate and methanol-water fractions. The were no significant changes in the body weight. Macropathological examination of the liver and kidneys showed normal results with a brownish red color, smooth surface and rubbery consistency. Histopathological examination revealed mild, moderate, and severe damage to the liver and kidneys of mice, however the level of damage was not followed by an increase in dose. The oral lethal dose was higher than 600 mg/Kg. Conclusion: Etlingera elatior (Jack) R.M. Sm did not produce toxic effects in mice after acute treatment.